The role of listening in e-contact center customer relationship management. Issue 1 (9th February 2015) - Park, JungKun; Chung, Te-Lin (Doreen); Gunn, Frances; Rutherford, Brian
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The main purpose of the study is to examine the relationships between e-listening and customers' perceptions of interpersonal service quality and utilitarian value during e-contact center interactions. Design/methodology/approach – Participants completed an online survey about their service experiences with e-contact centers. Data were analyzed using structural equation modeling. Findings – This study found that e-listening is highly related to interpersonal service quality and utilitarian value. Interpersonal service quality is positively related to e-satisfaction and e-loyalty, both with e-contact centers and e-retailers. Research limitations/implications – The study utilizes general active empathetic listening (AEL) constructs identified in previous research. Although these constructs provide a way to differentiate the cognitive aspects of AEL, and therefore, a mechanism for discerning utilitarian value, further qualitative studies on nonverbal cues in online communications would develop insights into more granular, behavioral dimensions and effects of e-listening. In addition, the study is based on general e-retailing processes, and is not focused on a specific business or sector. The magnitude of the effects of e-listening on the different factors related to customer relationships may vary with different sectors. Practical implications – E-contact centers should provide interpersonal interactions that emphasize utilitarian value. The centers should be staffed by employees who are well trained in AEL and who are provided with appropriate resources. The interactions of these e-contact centers can provide significant input to e-retailers about the improvement of service quality and resulting customer e-loyalty. Originality/value – The research provides an original view of service quality in e-contact center contexts and makes a valuable contribution to understanding the evolving service offerings of multi-channel e-retailing. The study provides support for the argument that value and quality in interpersonal interactions with e-contact centers lead to satisfaction and consequently to customer loyalty.